EFFECS OF THE CORPORATE CULTURE ON THE EMPLOYEEâS WORK PRODUCTIVITY PT PLN SURAKARTA IN FREE MARKET - Suseno, Yohanes Djoko (PROCEEDING INTERNASIONAL SEMINAR, 2015)
The main fabtor to adapt in the changing and competitive environment as well as to Improve performance was depending on enterpeiseâs competitive strength. Sustainbility of development operational management context on the lonf-term perspective, human resources have an important role to create and realizing business opportunity. Profesional employee that os able to achieve the task determined the high productivity . Competetive advantage of a company is its productivity.The objective of this research to anlyze effects of the corporate culture variables (integreity, professionalism, customer satisfaction, pattern, and reward to human resource) simultancously and partially, on employeeâs work productivity. Other analysis emphasizes on the dominant influential variables of corporate culture on employee;s work productivity.Design for this research used census technique to apllied in the PT PLN. Surakarta in free market, and select for 154 respondents and collecting data by questioners.Hypothesis examination imvolves multiple regression analysis. The result of this research indicate that integrity, professionalism, customer satisfaction, pattern, and reward to human resource simultaneously and partially have positive influrnce on employeeâs work productivity. This research result also shows that reward to human resource has the dominant influence on employee;s work productivity.PT PLN in free market.Keywords : corporate ,culture, employeeâs work productivity.